Persengkongkolan Perolehan Informasi Kegiatan Usaha dalam Hukum Persaingan Usaha - Rafi, Al Misky Muhammad; Tejomurti, Kukuh (Indonesian Publication Center, 2026)
Fair business competition is an important element in creating an efficient and equitable economic system. In modern business practices, competitive advantage is not only determined by production capacity or innovation but also by control over strategic information related to competitors’ business activities. Problems arise when such information is obtained through collusion with other parties, which may lead to unfair business competition. This study aims to analyze the fulfillment of the elements of collusion in obtaining business activity information and its legal implications under Indonesian competition law. This research uses normative legal research with statutory and conceptual approaches. The results show that such conduct may be classified as a violation if it fulfills the elements of business actors, collusion, the acquisition of competitors’ business information, and the potential to cause unfair business competition as stipulated in Article 23 of Law Number 5 of 1999.